Assessment on the occurrence and removal of Triclosan and Triclocarban from a wastewater treatment plant and their potential ecological risks - Musee, Ndeke (University of Pretoria, 2022)
Dissertation (MEng (Chemical Engineering))---University of Pretoria, 2022.